Expired concor drug as potential nontoxic corrosion inhibitor for 304 stainless steel in hydrochloric acid solution - Abd El Aziz S. Fouda; Azaly Ali M. El (Zaštita Materijala)
The effect of the expired concor drug as the corrosion inhibitor for stainless steel type 304 (304SS) in 2M HCl solution has been investigated using electrochemical and non-electrochemical techniques. Some kinetic corrosion parameters were calculated. The inhibition efficiency (% I) increases with rising concentration of the drug and maximum efficiency (85.8 %) reached 300 ppm. The polarization measurements indicated that the expired concor drug was of the mixed type and inhibits corrosion by adsorption on the surface of 304SS due to the presence of more than one active center in its molecule. The adsorption was obeyed Langmuir adsorption isotherm. The activation energy and thermodynamic parameters were also calculated and discussed.